(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
This paper analyzes main features of social recovery models, developed within the frameworks of Person-centered paradigm. Person- centeredness is an increasingly common public health and social care concept, that is used to describe a standard of care that ensures that the patient / client is at the center of care delivery. There is no single definition of person-centered care, rather we can find such terms as patient- centered, family-centered, user-centered, individualized. But irrespective of the terms used, a lot of research has looked at what matters to patients and how to provide personalized care to ensure that people have a good experience. Person-centered recovery depends on a number of aspects, in particular: the values of people and placing people at the center of care, taking into account the desires of people and the needs they have chosen, ensuring that people are emotionally comfortable and secure with family and friends, ensuring that people have access to the appropriate care they need, when and where they need to ensure that people receive all the care they need. Main principles of person-centered approach are: recognizing dignity, giving respect and compassion to service users and providers; collaboration with the individual, their family and staff in care planning and assessment; enabling systems and services to help people recognize and build on their own strengths, preferences and objectives in order to realize their full potential. One of the strongest and most methodologically grounded models built in the person-oriented framework is the Comprehensive Rehabilitation Approach (CARe), developed by Dirk den Hollander and Jean Pierre Wilken. The model is based on psychological rehabilitation, recovery and empowerment principles, and is intended to support individuals in their personal development. CARe works with the client in three domains: meeting quality of life wishes and objectives; overcoming insecurity and increasing strength; gaining access to ideal environments and optimizing the quality of life of living environments and social networks.